2019
DOI: 10.1186/s12974-019-1539-8
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal impairment following chronic Toxoplasma gondii infection is aggravated by intestinal nematode challenge in an IFN-γ-dependent manner

Abstract: Background It has become increasingly evident that the immune and nervous systems are closely intertwined, relying on one another during regular homeostatic conditions. Prolonged states of imbalance between neural and immune homeostasis, such as chronic neuroinflammation, are associated with a higher risk for neural damage. Toxoplasma gondii is a highly successful neurotropic parasite causing persistent subclinical neuroinflammation, which is associated with psychiatric … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 104 publications
7
32
0
Order By: Relevance
“…We also found that Hp burden was increased in HpTg animals. While others have not seen this, they have observed increased fecundity in the worms of the HpTg group [22],[94].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that Hp burden was increased in HpTg animals. While others have not seen this, they have observed increased fecundity in the worms of the HpTg group [22],[94].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these results were apparent only at 14 dpi indicating once again temporary repercussions in the nervous system upon peripheral inflammation. In this regard, our group has previously shown the effects of neuroinflammation on synapse integrity [55,80]. Given the reduced expression of genes associated with synapse neurotransmission we decided to test for adverse effects of IAV infection on synapse integrity.…”
Section: Discussionmentioning
confidence: 99%
“…IFN‐γ and several other cytokines such as IL‐6 are required to regulate T. gondii tachyzoite proliferation in the brain through microglial activation 40 . The expression of these cytokines, though important for T. gondii clearance, comes at the cost of prolonged neuroinflammation which alters the structural integrity of the brain compartments 41 . To this extent, finding the level of pro‐inflammatory cytokine that ensures parasitic clearance while mitigating neuroinflammation is desired.…”
Section: Discussionmentioning
confidence: 99%